THE COMPARISSON OF SPEAKING ABILITY USING PAIR DISCUSSION OF COOPERATIVE LEARNING AND REPETITION DRILL OF AUDIO LINGUAL METHOD AT DIFFERENT SELF-CONFIDENCES STUDENTS OF SMAN 1 RUMBIA ACADEMIC YEAR 2012/2013 - Tukir Wianto; Fachrudin Latif (Premise: Journal of English Education and Applied Linguistics, 2013)
This undergraduate thesis carries on as experimental study toward speaking ability at different self confidences. Since speaking needs correctness of pronunciation, form of the sentences uses and understandable dialogue. Here the students are expected to be able to speak in English with pronouncing an English word and the form of sentences well also making a better dialogue with their friends. To build the students speaking ability they can learn by practicing and repeating the words and structure of a sentence. The students speaking ability is also influenced by these self confidence.The purpose of this research is to find out the comparison average scores by applying Pair Discussion and Repetition Drill Technique at different self confidence. By applying the two techniques, students are expected to be able to speak confidently, pronounce the English word and along with the form of the sentences well. in this research, there are two classes of students the eleventh grade of SMA N 1 Rumbia as a sample.The finding of the result proves from experiment class which taught by Pair Discussion Technique find that students are able to pronounce and to form the sentences well, since this technique focus on discussion in pair as their practice to form the sentences and to pronounce of English words. While in the control class students taught by Repetition Drill Technique find that they are able to pronounce the sentence, since this technique focus on drill and repetition students are able to imitate the pronounce directly. But, by applying both of them, the students who have high and low self confidence have different result of speaking. It means that by applying two methods students can develop their speaking ability although in the different result of speaking ability.After conducting the research the researcher find that both Pair Discussion and Repetition Drill Technique are good to be applied for students in different self confidence, especially to develop the students’ speaking ability. The researcher expects to the English teachers have to be creative in conducting teaching learning technique so that students can interest in studying.